Ultrasound-Assisted Ferritin Extraction from Northern Pike Liver: An Innovative Approach for Chlorogenic Acid Encapsulation with Enhanced Thermal Stability - Zhikun Xing; Yi Wang; Yabo Wei; Xin Guo; Xiaoyue Liang; Xiaorong Deng; Lianfu Zhang; Jian Zhang (Molecules)
Ferritin, an emerging protein resource, has garnered significant attention in scientific research due to its biocompatibility and unique cavity structure capable of encapsulating bioactive compounds. This study aimed to optimize ultrasound-assisted extraction (UAE) for enhancing ferritin yield from northern pike liver byproducts and evaluate its potential as a nanocarrier for chlorogenic acid (CA). Through response surface methodology (RSM), the optimal UAE parameters were established as 200 W ultrasonic power, 1:3 solid–liquid ratio, and 25 min extraction time. Under these conditions, the ferritin extraction yield reached 139.46 mg/kg, representing a 4.02-fold increase compared to conventional methods (34.65 mg/mL). Electrophoretic analysis confirmed the electrophoretic purity of the extracted liver ferritin. Comprehensive characterization using UV-vis spectroscopy, FTIR, and fluorescence spectroscopy revealed preserved structural integrity of UAE-extracted ferritin. Homology modeling provided molecular insights into the ferritin architecture. Successful encapsulation of CA was achieved with an encapsulation efficiency of 13.25%, as quantified by HPLC. Analysis by DLS and ζ potential as well as TG and DSC showed that not only the thermal stability of CA was enhanced after ferritin encapsulation, but also that the ferritin remained stable with a cage-like structure. This investigation establishes UAE as an effective strategy for valorizing fish processing byproducts through high-yield ferritin extraction while demonstrating the protein’s functional capacity as a nanocarrier for bioactive compound delivery. The findings highlight the dual advantage of sustainable resource utilization and advanced delivery system development through this biotechnological approach.